Patterns of neighborhood environment attributes in relation to children's physical activity. (July 2015) - Kurka, Jonathan M.; Adams, Marc A.; Todd, Michael; Colburn, Trina; Sallis, James F.; Cain, Kelli L.; Glanz, Karen; Frank, Lawrence D.; Saelens, Brian E.
Abstract: Characterizing neighborhood environments in relation to physical activity is complex. Latent profiles of parents' perceptions of neighborhood characteristics were examined in relation to accelerometer-measured moderate-to-vigorous physical activity (MVPA) among 678 children (ages 6–12) in two US regions. Neighborhood environment profiles derived from walkability, transit access, aesthetics, crime and traffic safety, pedestrian infrastructure, and recreation/park access were created for each region. The San Diego County profile lowest on walkability and recreation/park access was associated with an average of 13 fewer min/day of children's out-of-school MVPA compared to profiles higher on walkability and recreation/park access. Seattle/King County profiles did not differ on children's MVPA. Neighborhood environment profiles were associated with children's MVPA in one region, but results were inconsistent across regions.